High-conductivity oxygen etched graphene copper composite material and preparation method thereof
Through oxygen plasma etching and vacuum hot pressing technology, the problem of poor conductivity improvement effect of traditional graphene copper composite materials is solved, and the high conductivity and strengthening mechanical properties of graphene copper composite materials are achieved.
Patent Information
- Application Number
- CN202411723520.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The conductivity improvement effect of traditional graphene copper composite materials is poor, mainly because it is difficult to bond between atoms between copper and carbon, resulting in poor bonding between the copper layer and the graphene layer and poor electron transport effect between layers.
The graphene layer of graphene copper foil is processed by oxygen plasma etching technology to remove impurities and introduce oxygen atoms, so that the oxygen atoms narrow the spacing between the copper base layer and the graphene layer through covalent bridging, and increase the bonding strength. Then, bonding is achieved between two adjacent layers of graphene copper foils by vacuum hot pressing to form an oxygen-etched graphene copper composite material.
By increasing the bonding strength between the copper-carbon layers, the conductivity of graphene copper composite material is significantly improved and the overall performance of the material is further improved.
Smart Images

Figure CN119553245A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite material preparation, and in particular to a high-conductivity oxygen-etched graphene copper composite material and a preparation method thereof. Background Art
[0002] Copper is a metal with the second best conductivity after silver. It has stable chemical properties, has been widely studied, and its reserves and preparation costs are far lower than silver. It is currently the most consumed and widely used conductive material in society.
[0003] Copper has been used in wires, cables, copper contact materials, and various electrical appliances in many fields such as electrical electronics, national defense and military industry, power transmission and power generation, and aerospace. The electrical conductivity of metallic copper materials determines key indicators such as engine motor loss, conductive cable weight, and electronic circuit substrate efficiency. Further improvement of the electrical conductivity of copper materials is of great significance for reducing transmission losses, reducing the weight of aerospace equipment, and improving mechanical properties. Traditional methods for improving the conductivity of metals include purification and single crystallization, which have been raised to the upper limit in recent years. By reducing impurities and single crystallization in copper, the conductivity of pure copper can be increased to 103% IACS, but the cost increases significantly. It is hoped that the conductivity of copper can be further enhanced by adding other metals or non-metallic materials to copper to form a composite.
[0004] Graphene is a two-dimensional material with a honeycomb carbon atom structure. It was first successfully prepared in 20024. The special structure of graphene gives it an extremely high carrier mobility (15000cm 2 / (V·S)) and excellent mechanical properties (Young's modulus of 1100Gpa and fracture strength of 130Gpa). Therefore, graphene is regarded as an ideal composite material reinforcement, which has the potential to further optimize copper conductivity and enhance mechanical properties.
[0005] Graphene copper composites have the advantages of high mobility of graphene and high conductive electron density of copper. Due to the mechanical strength of graphene itself, they have the advantages of high conductivity and high strength. The traditional preparation methods of graphene copper composites mainly include powder metallurgy and hot isostatic pressing. However, since graphene is already incomplete, a second phase is formed in copper, which hinders the transmission of electrons. The conductivity enhancement effect of graphene copper composites prepared by powder metallurgy is not good, and the conductivity will be reduced in most experiments. Among them, hot isostatic pressing can maintain the integrity of the graphene structure, retain the high mobility of graphene, and effectively compound copper and graphene together. The obtained layered graphene copper composite has a very high conductivity. However, the graphene copper composite obtained by this method has poor bonding between copper and carbon atoms, poor bonding between copper layer and graphene layer, large interlayer spacing, and poor interlayer electron transmission effect, which hinders the further improvement of the conductivity of graphene copper composites. Summary of the invention
[0006] The present invention provides a method for preparing a high-conductivity oxygen-etched graphene copper composite material, which specifically includes the following steps: S1: preparing a graphene copper foil, wherein the graphene copper foil comprises a copper base layer, and graphene layers are deposited on both sides of the copper base layer by chemical vapor deposition; S2: using plasma etching technology to perform oxygen plasma etching on the graphene layers on both sides of the graphene copper foil to form oxygen-etched graphene copper foil; S3: stacking two or more layers of oxygen-etched graphene copper foil obtained in step S2 in layers, and aligning the back surface of the upper layer of oxygen-etched graphene copper foil with the front surface of the lower layer of oxygen-etched graphene copper foil to obtain a multilayer oxygen-etched graphene copper foil material; S4: vacuum hot pressing the multi-layer oxygen-etched graphene copper foil material in step S3 to achieve bonding between two adjacent layers of graphene copper foil to obtain an oxygen-etched graphene copper composite material.
[0007] The present invention is further configured as follows: the copper base layer in step S1 has a thickness of 20-50 μm, and the graphene monolayer coverage deposited on the copper base layer is ≥50%.
[0008] The present invention is further configured as follows: the oxygen flow rate used in the oxygen plasma etching in step S2 is 15 sccm, the plasma processing power is 20-60w, and the processing time is 2-25s.
[0009] The present invention is further configured as follows: the oxygen plasma etching process in step S2 is performed in a vacuum environment.
[0010] The present invention is further configured as follows: in step S3, the number of stacked layers of oxygen-etched graphene copper foil is 10-200 layers.
[0011] The present invention is further configured as follows: in step S4, the hot pressing pressure is 100 MPa, the hot pressing temperature is 1000° C., and the hot pressing time is 30 min.
[0012] The present invention is further configured as follows: the vacuum degree of the hot pressing in step S4 is less than 5×10 -3 Pa.
[0013] The present invention is further configured as follows: during the process from step S2 to step S4, the graphene copper foil is stored or treated in a vacuum or inert atmosphere from the completion of the oxygen plasma treatment to the end of the vacuum hot pressing.
[0014] The present invention is further configured as follows: the graphene copper foil is stored or treated in an inert atmosphere from the completion of the oxygen plasma treatment to the completion of the vacuum hot pressing.
[0015] The present invention also provides a high-conductivity oxygen-etched graphene copper composite material, which is prepared by the above preparation method.
[0016] The beneficial effects of the present invention are:
[0017] 1. By using oxygen plasma etching to process the graphene layer of the graphene copper foil, impurities and dust left on the graphene surface during the chemical vapor deposition and transfer process can be removed, thereby achieving the effect of cleaning the surface of the material and further avoiding the introduction of other impurity atoms. The presence of the graphene layer can protect the underlying copper base layer and prevent the copper base layer from being oxidized.
[0018] 2. Oxygen atoms are introduced near the interface between the graphene layer and the copper base layer, and oxygen can form copper-oxygen and carbon-oxygen groups with copper and carbon. Oxygen atoms shorten the distance between the copper base layer and the graphene layer through covalent bridging, and the low-intensity van der Waals interaction between the layers is changed to covalent interaction, and the bonding strength is significantly improved. The enhanced copper-carbon bonding lowers the migration barrier of electrons between the copper base layer and the graphene layer, and the enhanced conductivity of graphene copper is better, further improving the conductivity of the oxygen-etched graphene-copper composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 A schematic diagram of Raman characterization of the results before and after etching of Example 2 is shown.
[0020] Figure 2 A schematic diagram of Raman characterization of the results before and after etching of Example 3 is shown.
[0021] Figure 3 A schematic diagram of Raman characterization of the results before and after etching of Example 4 is shown.
[0022] Figure 4 A schematic diagram of SEM characterization of the results before and after etching is shown. DETAILED DESCRIPTION
[0023] Those skilled in the art can refer to the content of this article and appropriately improve the process parameters. It is particularly important to point out that all similar replacements and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.
[0024] Example 1
[0025] The present invention provides a method for preparing a high-conductivity oxygen-etched graphene copper composite material, which specifically comprises the following steps:
[0026] S1: preparing a graphene copper foil, wherein the graphene copper foil comprises a copper base layer, and both sides of the copper base layer are provided with a graphene layer by chemical vapor deposition;
[0027] S2: using plasma etching technology, performing oxygen plasma etching on the graphene layers on both sides of the graphene copper foil to form oxygen-etched graphene copper foil;
[0028] S3: stacking two or more layers of oxygen-etched graphene copper foil obtained in step S2 in layers, and aligning the back surface of the upper layer of oxygen-etched graphene copper foil with the front surface of the lower layer of oxygen-etched graphene copper foil, that is, the back surface of the upper layer is in contact with the front surface of the lower layer, so as to obtain a multilayer oxygen-etched graphene copper foil material;
[0029] S4: vacuum hot pressing the multi-layer oxygen-etched graphene copper foil material in step S3 to achieve bonding between two adjacent layers of graphene copper foil to obtain an oxygen-etched graphene copper composite material.
[0030] The thickness of the copper base layer in step S1 is 20-50 μm, and the coverage of the graphene monolayer deposited on the copper base layer is ≥50%.
[0031] The oxygen flow rate used in oxygen plasma etching in step S2 is 15 sccm, the plasma processing power is 20-60w, and the processing time is 2-25s.
[0032] The oxygen plasma etching process in step S2 is performed in a vacuum environment.
[0033] The number of stacked layers of oxygen-etched graphene copper foil in step S3 is 10-200 layers.
[0034] In step S4, the hot pressing pressure is 100 MPa, the hot pressing temperature is 1000° C., and the hot pressing time is 30 min.
[0035] The vacuum degree of hot pressing in step S4 is less than 5×10 -3 Pa.
[0036] In the process from step S2 to step S4, the graphene copper foil is stored or processed in a vacuum or inert atmosphere throughout the entire process from the completion of oxygen plasma treatment to the end of vacuum hot pressing. In the present application, an inert atmosphere is selected for storage or processing.
[0037] Example 2
[0038] This embodiment adopts the preparation method of embodiment 1 to prepare the graphene copper composite material, which specifically includes the following steps:
[0039] S1: preparing a copper foil with a thickness of 25 μm, and depositing a graphene layer on both sides of the copper foil by chemical vapor deposition, with a single layer coverage of 90%, to prepare a graphene copper foil.
[0040] S2: In a reactive ion etching (RIE) machine, the graphene layers on both sides of the graphene copper foil were treated with oxygen ions at an oxygen flow rate of 15 sccm and a power of 50 W. Each side was treated for 10 seconds to form an oxygen-etched graphene copper foil. The results before and after oxygen etching were characterized by Raman. Figure 1 As shown, the G peak and G' peak weaken to produce the D peak representing the defect. The structure before and after oxygen etching was characterized by scanning electron microscopy (SEM). The results are shown in Figure 4 shown.
[0041] S3: Cut the oxygen-etched graphene copper foil obtained in step S2 into standard squares of about 2 cm×2 cm in size, and stack 16 layers of the oxygen-etched graphene copper foil obtained in step S2 with their front sides facing each other, that is, the back side of the upper layer of oxygen-etched graphene copper foil is aligned with the front side of the lower layer of oxygen-etched graphene copper foil, so that the back side of the upper layer is in contact with the front side of the lower layer, so as to obtain a multi-layer stacked oxygen-etched graphene copper foil material.
[0042] S4: The front side of the top layer and the back side of the bottom layer of the oxygen-etched graphene copper foil material stacked in step S3 are uniformly covered with graphite lubricant, and placed in a vacuum hot pressing furnace, and hot pressed for 30 minutes at a temperature of 1000°C and a uniform pressure of 100Mpa. After the hot pressing is completed, the pressure is maintained, and the temperature is naturally lowered for 40 minutes, and the graphene copper composite material is taken out to obtain.
[0043] It should be noted that during the process from the completion of oxygen plasma treatment to the end of vacuum hot pressing, the graphene copper foil is stored or treated in an inert atmosphere except inside and outside the vacuum hot pressing furnace.
[0044] The graphene copper composite material was polished to remove the residual graphene on the surface and cut into 2 cm × 2 cm squares. The size was measured to be 2.005 cm × 2.021 cm and the thickness was 0.374 mm. The electrical conductivity was measured by the Van der Pauw method to be 120.2% IACS.
[0045] Example 3
[0046] This embodiment adopts the preparation method of embodiment 1 to prepare the graphene copper composite material, which specifically includes the following steps:
[0047] S1: preparing a copper foil with a thickness of 25 μm, and depositing a graphene layer on both sides of the copper foil by chemical vapor deposition, with a single layer coverage of 80%, to prepare a graphene copper foil.
[0048] S2: In a reactive ion etching (RIE) machine, the graphene layers on both sides of the graphene copper foil were treated with oxygen ions at an oxygen flow rate of 15 sccm and a power of 50 W. Each side was treated for 15 s to form an oxygen-etched graphene copper foil. The results before and after oxygen etching were characterized by Raman. Figure 2 shown.
[0049] S3: Cut the oxygen-etched graphene copper foil obtained in step S2 into standard squares of about 2 cm×2 cm in size, and stack 32 layers of the oxygen-etched graphene copper foil obtained in step S2 with their front sides facing each other, that is, the back side of the upper layer of oxygen-etched graphene copper foil is aligned with the front side of the lower layer of oxygen-etched graphene copper foil, so that the back side of the upper layer is in contact with the front side of the lower layer, so as to obtain a multi-layer stacked oxygen-etched graphene copper foil material.
[0050] S4: The front side of the top layer and the back side of the bottom layer of the oxygen-etched graphene copper foil material stacked in step S3 are uniformly covered with graphite lubricant, and placed in a vacuum hot pressing furnace, and hot pressed for 30 minutes at a temperature of 1000°C and a uniform pressure of 100Mpa. After the hot pressing is completed, the pressure is maintained, and the temperature is naturally lowered for 40 minutes, and the graphene copper composite material is taken out to obtain.
[0051] It should be noted that during the process from the completion of oxygen plasma treatment to the end of vacuum hot pressing, the graphene copper foil is stored or treated in an inert atmosphere except inside and outside the vacuum hot pressing furnace.
[0052] The graphene copper composite material was polished to remove the residual graphene on the surface and cut into 2 cm × 2 cm squares. The size was measured to be 2.020 cm × 2.008 cm and the thickness was 0.717 mm. The electrical conductivity was measured by the Van der Pauw method to be 119.4% IACS.
[0053] Example 4
[0054] This embodiment adopts the preparation method of embodiment 1 to prepare the graphene copper composite material, which specifically includes the following steps:
[0055] S1: preparing a copper foil with a thickness of 50 μm, and depositing a graphene layer on both sides of the copper foil by chemical vapor deposition, with a single layer coverage of 95%, to prepare a graphene copper foil.
[0056] S2: In a reactive ion etching (RIE) machine, the graphene layers on both sides of the graphene copper foil were treated with oxygen ions at an oxygen flow rate of 15 sccm and a power of 30w. Each side was treated for 10 seconds to form oxygen-etched graphene copper foil. The results before and after oxygen etching were characterized by Raman. The results are referenced to Figure 3 shown.
[0057] S3: Cut the oxygen-etched graphene copper foil obtained in step S2 into standard squares of about 2 cm×2 cm in size, and stack 16 layers of the oxygen-etched graphene copper foil obtained in step S2 with their front sides facing each other, that is, the back side of the upper layer of oxygen-etched graphene copper foil is aligned with the front side of the lower layer of oxygen-etched graphene copper foil, so that the back side of the upper layer is in contact with the front side of the lower layer, so as to obtain a multi-layer stacked oxygen-etched graphene copper foil material.
[0058] S4: The front side of the top layer and the back side of the bottom layer of the oxygen-etched graphene copper foil material stacked in step S3 are uniformly covered with graphite lubricant, and placed in a vacuum hot pressing furnace, and hot pressed for 30 minutes at a temperature of 1000°C and a uniform pressure of 100Mpa. After the hot pressing is completed, the pressure is maintained, and the temperature is naturally lowered for 40 minutes, and the graphene copper composite material is taken out to obtain.
[0059] It should be noted that during the process from the completion of oxygen plasma treatment to the end of vacuum hot pressing, the graphene copper foil is stored or treated in an inert atmosphere except inside and outside the vacuum hot pressing furnace.
[0060] The graphene copper composite material was polished to remove the residual graphene on the surface and cut into 2 cm × 2 cm squares. The size was measured to be 1.984 cm × 2.017 cm and the thickness was 0.742 mm. The electrical conductivity was measured by the Van der Pauw method to be 118.0% IACS.
[0061] Example 5
[0062] This embodiment adopts the preparation method of embodiment 1 to prepare the graphene copper composite material, which specifically includes the following steps:
[0063] S1: preparing a copper foil with a thickness of 20 μm, and depositing a graphene layer on both sides of the copper foil by chemical vapor deposition, with a single layer coverage of 90%, to prepare a graphene copper foil.
[0064] S2: In a reactive ion etching (RIE) machine, the graphene layers on both sides of the graphene copper foil were treated with oxygen ions at an oxygen flow rate of 15 sccm and a power of 50 W. Each side was treated for 10 seconds to form an oxygen-etched graphene copper foil. The results before and after oxygen etching were characterized by Raman. Figure 3 shown.
[0065] S3: Cut the oxygen-etched graphene copper foil obtained in step S2 into standard squares of about 2 cm×2 cm in size, and stack 16 layers of the oxygen-etched graphene copper foil obtained in step S2 with their front sides facing each other, that is, the back side of the upper layer of oxygen-etched graphene copper foil is aligned with the front side of the lower layer of oxygen-etched graphene copper foil, so that the back side of the upper layer is in contact with the front side of the lower layer, so as to obtain a multi-layer stacked oxygen-etched graphene copper foil material.
[0066] S4: The front side of the top layer and the back side of the bottom layer of the oxygen-etched graphene copper foil material stacked in step S3 are uniformly covered with graphite lubricant, and placed in a vacuum hot pressing furnace, and hot pressed for 30 minutes at a temperature of 1000°C and a uniform pressure of 100Mpa. After the hot pressing is completed, the pressure is maintained, and the temperature is naturally lowered for 40 minutes, and the graphene copper composite material is taken out to obtain.
[0067] It should be noted that during the process from the completion of oxygen plasma treatment to the end of vacuum hot pressing, the graphene copper foil is stored or treated in an inert atmosphere except inside and outside the vacuum hot pressing furnace.
[0068] The graphene copper composite material was polished to remove the residual graphene on the surface and cut into 2 cm × 2 cm squares. The size was measured to be 1.994 cm × 2.007 cm and the thickness was 0.742 mm. The electrical conductivity was measured by the Van der Pauw method to be 119.6% IACS.
[0069] Example 6
[0070] This embodiment adopts the preparation method of embodiment 1 to prepare the graphene copper composite material, which specifically includes the following steps:
[0071] S1: preparing a copper foil with a thickness of 25 μm, and depositing a graphene layer on both sides of the copper foil by chemical vapor deposition, with a single layer coverage of 90%, to prepare a graphene copper foil.
[0072] S2: In a reactive ion etching (RIE) machine, the graphene layers on both sides of the graphene copper foil were treated with oxygen ions at an oxygen flow rate of 15 sccm and a power of 45 W. Each side was treated for 10 seconds to form an oxygen-etched graphene copper foil. The results before and after oxygen etching were characterized by Raman. Figure 3 shown.
[0073] S3: Cut the oxygen-etched graphene copper foil obtained in step S2 into standard squares of about 2 cm×2 cm in size, and stack 16 layers of the oxygen-etched graphene copper foil obtained in step S2 with their front sides facing each other, that is, the back side of the upper layer of oxygen-etched graphene copper foil is aligned with the front side of the lower layer of oxygen-etched graphene copper foil, so that the back side of the upper layer is in contact with the front side of the lower layer, so as to obtain a multi-layer stacked oxygen-etched graphene copper foil material.
[0074] S4: The front side of the top layer and the back side of the bottom layer of the oxygen-etched graphene copper foil material stacked in step S3 are uniformly covered with graphite lubricant, and placed in a vacuum hot pressing furnace, and hot pressed for 30 minutes at a temperature of 1000°C and a uniform pressure of 100Mpa. After the hot pressing is completed, the pressure is maintained, and the temperature is naturally lowered for 40 minutes, and the graphene copper composite material is taken out to obtain.
[0075] It should be noted that during the process from the completion of oxygen plasma treatment to the end of vacuum hot pressing, the graphene copper foil is stored or treated in an inert atmosphere except inside and outside the vacuum hot pressing furnace.
[0076] The graphene copper composite material was polished to remove the residual graphene on the surface and cut into 2 cm × 2 cm squares. The size was measured to be 2.011 cm × 2.027 cm and the thickness was 0.742 mm. The electrical conductivity was measured by the Van der Pauw method to be 119.1% IACS.
[0077] Example 7
[0078] This embodiment adopts the preparation method of embodiment 1 to prepare the graphene copper composite material, which specifically includes the following steps:
[0079] S1: preparing a copper foil with a thickness of 25 μm, and depositing a graphene layer on both sides of the copper foil by chemical vapor deposition, with a single layer coverage of 90%, to prepare a graphene copper foil.
[0080] S2: In a reactive ion etching (RIE) machine, the graphene layers on both sides of the graphene copper foil were treated with oxygen ions at an oxygen flow rate of 15 sccm and a power of 50w. Each side was treated for 2s to form an oxygen-etched graphene copper foil. The results before and after oxygen etching were characterized by Raman. The results are referenced to Figure 3 shown.
[0081] S3: Cut the oxygen-etched graphene copper foil obtained in step S2 into standard squares of about 2 cm×2 cm in size, and stack 16 layers of the oxygen-etched graphene copper foil obtained in step S2 with their front sides facing each other, that is, the back side of the upper layer of oxygen-etched graphene copper foil is aligned with the front side of the lower layer of oxygen-etched graphene copper foil, so that the back side of the upper layer is in contact with the front side of the lower layer, so as to obtain a multi-layer stacked oxygen-etched graphene copper foil material.
[0082] S4: The front side of the top layer and the back side of the bottom layer of the oxygen-etched graphene copper foil material stacked in step S3 are uniformly covered with graphite lubricant, and placed in a vacuum hot pressing furnace, and hot pressed for 30 minutes at a temperature of 1000°C and a uniform pressure of 100Mpa. After the hot pressing is completed, the pressure is maintained, and the temperature is naturally lowered for 40 minutes, and the graphene copper composite material is taken out to obtain.
[0083] It should be noted that during the process from the completion of oxygen plasma treatment to the end of vacuum hot pressing, the graphene copper foil is stored or treated in an inert atmosphere except inside and outside the vacuum hot pressing furnace.
[0084] The graphene copper composite material was polished to remove the residual graphene on the surface and cut into 2 cm × 2 cm squares. The size was measured to be 2.001 cm × 2.012 cm and the thickness was 0.742 mm. The electrical conductivity was measured by the Van der Pauw method to be 116.8% IACS.
[0085] Example 8
[0086] This embodiment adopts the preparation method of embodiment 1 to prepare the graphene copper composite material, which specifically includes the following steps:
[0087] S1: preparing a copper foil with a thickness of 25 μm, and depositing a graphene layer on both sides of the copper foil by chemical vapor deposition, with a single layer coverage of 90%, to prepare a graphene copper foil.
[0088] S2: In a reactive ion etching (RIE) machine, the graphene layers on both sides of the graphene copper foil were treated with oxygen ions at an oxygen flow rate of 15 sccm and a power of 50 W. Each side was treated for 25 seconds to form an oxygen-etched graphene copper foil. The results before and after oxygen etching were characterized by Raman. Figure 3 shown.
[0089] S3: Cut the oxygen-etched graphene copper foil obtained in step S2 into standard squares of about 2 cm×2 cm in size, and stack 16 layers of the oxygen-etched graphene copper foil obtained in step S2 with their front sides facing each other, that is, the back side of the upper layer of oxygen-etched graphene copper foil is aligned with the front side of the lower layer of oxygen-etched graphene copper foil, so that the back side of the upper layer is in contact with the front side of the lower layer, so as to obtain a multi-layer stacked oxygen-etched graphene copper foil material.
[0090] S4: The front side of the top layer and the back side of the bottom layer of the oxygen-etched graphene copper foil material stacked in step S3 are uniformly covered with graphite lubricant, and placed in a vacuum hot pressing furnace, and hot pressed for 30 minutes at a temperature of 1000°C and a uniform pressure of 100Mpa. After the hot pressing is completed, the pressure is maintained, and the temperature is naturally lowered for 40 minutes, and the graphene copper composite material is taken out to obtain.
[0091] It should be noted that during the process from the completion of oxygen plasma treatment to the end of vacuum hot pressing, the graphene copper foil is stored or treated in an inert atmosphere except inside and outside the vacuum hot pressing furnace.
[0092] The graphene copper composite material was polished to remove the residual graphene on the surface and cut into 2 cm × 2 cm squares. The size was measured to be 2.110 cm × 2.112 cm and the thickness was 0.742 mm. The electrical conductivity was measured by the Van der Pauw method to be 114.3% IACS.
[0093] Example 9
[0094] This embodiment discloses a high-conductivity oxygen-etched graphene copper composite material, which is prepared by the above-mentioned preparation method.
[0095] In summary, the present invention processes the graphene layer of the graphene copper foil by utilizing oxygen plasma etching, thereby removing impurities and dust left on the graphene surface during the chemical vapor deposition and transfer process, thereby achieving the effect of cleaning the surface of the material and further avoiding the introduction of other impurity atoms. The presence of the graphene layer can protect the underlying copper base layer and prevent the copper base layer from being oxidized.
[0096] Oxygen atoms are introduced near the interface between the graphene layer and the copper-based layer, and oxygen can form copper-oxygen and carbon-oxygen groups with copper and carbon. The oxygen atoms shorten the distance between the copper-based layer and the graphene layer through covalent bridging, and the low-intensity van der Waals interaction between the layers is changed to covalent interaction, and the bonding strength is significantly improved. The enhanced copper-carbon bonding lowers the migration barrier of electrons between the copper-based layer and the graphene layer, and the enhanced conductivity of graphene-copper is better, further improving the conductivity of the oxygen-etched graphene-copper composite material.
[0097] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be within the scope of protection of the present invention.
Claims
1. A method for preparing a highly conductive oxygen-etched graphene copper composite material, characterized in that: The specific steps include: S1: preparing a graphene copper foil, wherein the graphene copper foil comprises a copper base layer, and graphene layers are deposited on both sides of the copper base layer by chemical vapor deposition; S2: using plasma etching technology to perform oxygen plasma etching on the graphene layers on both sides of the graphene copper foil to form oxygen-etched graphene copper foil; S3: stacking two or more layers of oxygen-etched graphene copper foil obtained in step S2 in layers, and aligning the back surface of the upper layer of oxygen-etched graphene copper foil with the front surface of the lower layer of oxygen-etched graphene copper foil to obtain a multilayer oxygen-etched graphene copper foil material; S4: vacuum hot pressing the multi-layer oxygen-etched graphene copper foil material in step S3 to achieve bonding between two adjacent layers of graphene copper foil to obtain an oxygen-etched graphene copper composite material.
2. The method for preparing the high-conductivity oxygen-etched graphene copper composite material according to claim 1, characterized in that: The copper base layer in step S1 has a thickness of 20-50 μm, and the coverage of the graphene monolayer deposited on the copper base layer is ≥50%.
3. The method for preparing the high-conductivity oxygen-etched graphene copper composite material according to claim 1, characterized in that: The oxygen flow rate used in the oxygen plasma etching in step S2 is 15 sccm, the plasma processing power is 20-60w, and the processing time is 2-25s.
4. The method for preparing the high-conductivity oxygen-etched graphene copper composite material according to claim 3, characterized in that: The oxygen plasma etching process in step S2 is performed in a vacuum environment.
5. The method for preparing the high-conductivity oxygen-etched graphene copper composite material according to claim 1, characterized in that: In the step S3, the number of stacked layers of oxygen-etched graphene copper foil is 10-200 layers.
6. The method for preparing the high-conductivity oxygen-etched graphene copper composite material according to claim 1, characterized in that: In step S4, the hot pressing pressure is 100 MPa, the hot pressing temperature is 1000° C., and the hot pressing time is 30 min.
7. The method for preparing the high-conductivity oxygen-etched graphene copper composite material according to claim 6, characterized in that: The vacuum degree of hot pressing in step S4 is less than 5×10 -3 Pa.
8. The method for preparing the high-conductivity oxygen-etched graphene copper composite material according to claim 1, characterized in that: During the process from step S2 to step S4, the graphene copper foil is stored or treated in a vacuum or inert atmosphere from the completion of the oxygen plasma treatment to the end of the vacuum hot pressing.
9. The method for preparing the high-conductivity oxygen-etched graphene copper composite material according to claim 8, characterized in that: The graphene copper foil is stored or processed in an inert atmosphere from the completion of oxygen plasma treatment to the end of vacuum hot pressing.
10. A highly conductive oxygen-etched graphene copper composite material, characterized in that: The method is prepared according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method for transferring graphene by using micro-molecule paraffin
CN106477570A
Acceleration sensor based on graphene suspended mass block and preparation method thereof
CN117723780A
Preparing method of diamond like carbon film using hydrogen plasma
KR1020150145746A
Process for forming homoepitaxial tunnel barriers with hydrogenated graphene-on-graphene for room temperature electronic device applications
US20180130897A1
Cited By
Method for preparing ultrahigh-conductivity graphene / copper composite material through nitrogen plasma ball milling
CN121911876A